Second five-year follow-up after a booster vaccination against tick-borne encephalitis following different primary vaccination schedules demonstrates at least 10 years antibody persistence - Beran, Jiri; Lattanzi, Maria; Xie, Fang; Moraschini, Luca; Galgani, Ilaria (Vaccine, 2019)
BACKGROUND: Tick borne encephalitis (TBE) endemic zones are expanding. We previously evaluated long term persistence of antibody 5 years after the first booster immunization following different primary immunization schedules with the polygeline-free inactivated TBE vaccine (TBEvac) in adults and adolescents. Here, we report anti-TBE virus (TBEV) antibody persistence from 6 to 10 years post-booster administration. METHODS: This was a phase IV, open-label, single-center, second extension study (NCT01562444), conducted in Czechia. Healthy adults and adolescents ≥12 years who had received 3 different primary vaccination schedules (rapid, conventional and accelerated conventional) in the parent study and a booster dose before (12-18 months post-primary series completion) or at the beginning (3 years post-primary series completion) of the first extension study were screened and enrolled in this study. Blood samples were collected yearly and anti-TBEV antibody response was evaluated by neutralizing test (NT) antibody assays. Analysis was performed overall and per age strata: 15-49 years, ≥50 years, and ≥60 years. RESULTS: Of 206 screened individuals, 191 completed the study. Overall, 90-100% of participants in the all-screened set and ≥97% in the per-protocol set had the clinically meaningful threshold of protection (NT titers ≥10) across all timepoints, regardless of the primary vaccination schedule. Overall, antibody geometric mean titers (GMTs) varied from 134 to 343 in the all-screened set. Older age groups showed overall lower GMTs, although GMTs remained higher than NT titers ≥10 up to year 10 in all groups. CONCLUSION: This study showed long-term persistence of anti-TBEV NT antibodies for up to 10 years after the first booster dose of TBEvac in all age groups, regardless of the primary vaccination schedule.
Keywords: klíšťová encefalitida; následné studie; lidé; mladiství; Adult; Middle Aged; Antibodies, Neutralizing; Adults; Encepur; Encephalitis, Tick-Borne; Long-term persistence; Female; dítě; sekundární imunizace; Tick-borne encephalitis; Booster; Viral Vaccines; Adolescent; Humans; Follow-Up Studies; Immunization Schedule; Antibodies, Viral; Česká republika; očkovací schéma; viry klíšťové encefalitidy; lidé středního věku; mužské pohlaví; mladý dospělý; neutralizující protilátky; Immunization, Secondary; Time Factors; Czech Republic; ženské pohlaví; virové vakcíny; Encephalitis Viruses, Tick-Borne; Young Adult; Aged, 80 and over; protilátky virové; senioři nad 80 let; časové faktory; Aged; Male; Child; dospělí; senioři